Study Effect of Supplementation of Two Types Omega 3 Fatty Acids on Lipid Profile of Asthmatics. - Mahdi, Sarah A (Al-Nahrain Journal of Science, 2018)
Asthma is a chronic worldwide disorder. Recent studies refer to association between asthma and major CVD incidence, which the abnormality of lipid profile is a direct indicator to this type of disease. The aim of this study is measuring the lipids levels in asthmatics and evaluates the omega 3 fatty acid effects on lowering its levels in asthmatics sera. Twenty five asthmatic patients (10 females and 15 males) were involved compared with 25 healthy controls. Serum samples analyzed for total cholesterol, triglycerides, high density lipoprotein, low density lipoprotein, and very low density lipoprotein. Before and after 3 weeks of supplementation of two types omega-3 polyunsaturated fatty acids (300mg/day) (4 weeks of follow up.) After 3 weeks of supplementation the change in levels of lipid profile.